Validity of Rental Agreement for Renting Land of Reward Between Village Head with Private Parties Who Exceed The Term of Office Village Head - Agustina, Enno Sellya; Anshari, Tunggul; Widiarto, Aan Eko (International Journal of Business, Law, and Education, 2024)
Based on the issues related to the lease of reward land between the village chief and a private party that exceeds the chief's term, this paper aims to analyze the legality of the lease agreement for reward land between the village chief and a private party that extends beyond his term of office. In this paper, the researcher uses a normative juridical method, along with a legislative and case study approach. Then, with this analysis, the researcher can address the raised issue about the legality of the lease agreement for reward land between the village chief. From these issues, it can be concluded that the legality of the lease agreement for reward land between the village chief and a private party is regulated in Permendagri Number 1 of 2016 concerning the Management of Village Assets, with the maximum lease limit for reward land being a maximum of 3 (three) years. If there is a lease agreement for reward land between the village chief and a private party that exceeds the chief's term of office, then the agreement is legally void.